PENGEMBANGAN PERANGKAT ASESMEN KINERJA DALAM PEMBELAJARAN MATEMATIKA SUB POKOK BAHASAN MELUKIS SEGITIGA PADA SISWA KELAS VII SMP NEGERI 2 SURABAYA - Zaki, Muhammad (Jurnal Ilmiah AdMathEdu, 2012)
Paper and pencil test has been said to have failed to provide a robust indication of students competence achievement. NCTM for instance maintains that a practical math assessment is needed for such a purpose. To measure students performance requires an alternative assessment instrument. An instrument which is not depending on a mere writing test alone (paper and pencil test), as underlined in KTSP. KTSP is a class-based assessment, which also calls for a throughout assessment through which students are asked to demonstrate their learned competence in more ways than one. As an alternative assessment, Performance assessment is too a class based assessment, consisting of two difference parts namely performance and rubric task. The former is referred to those open questions which necessitate students to solve them by showing the process (performance) of how they are done while the latter sets the guideline for grading and scoring students performance, based on assessment criteria which has been earlier prepared. Performance assessment is undertaken to particularly review and assess students tasks using which teachers could comprehend and collect thorough information regarding students knowledge of math, math strategies and communication. This research has been carried out to intentionally measure how math achievement of secondary school students has met its learning goal especially in sub-topics of triangle drawing using performance assessment. The data for this research were collected at SMP Negeri 2 Surabaya. This topic was purposely selected and deemed appropriate to comprehend students ability as it requires them to show their best ability to use anchor  and  ruler as well as how they appropriately follow steps in the process. The research question is how software development processes and results of performance assessment in mathematics learning in class VII students of SMP Negeri 2 Surabaya?. Based on the research questions above, then the purpose of this study was to describe the development and yield performance assessment tools in learning mathematics for class VII students of SMP Negeri 2 Surabaya. Subjects tested in this study is that VII H grade students represented by six students and VII B grade students as subjects for the implementation of performance assessment instrument. To answer the research questions above, this study was designed to study the development in accordance with fase model of development on the Plomp. This study used the instrument in the form of task performance, assessment rubrics, guidelines for student interviews and questionnaires. Data collection techniques used in this study is to provide the task performance, questionnaires, and interviews. The research found that the development of assessment performance instrument using  plomp development model on the sub-topic of triangle drawing will require five different phases, namely 1) initial investigation, 2). Planning, construction realization, test, evaluation and revision, and 5) implementation. Using plomp development model, a set of task performance assessment was produced in relation to triangle drawing sub-topic. it was stated that this task performance assessment:  (1) is Valid under in the view of the experts, (2) that the difficulty level of assessment task was low. The same is too found in rubric assessment.(3) that  the students could entirely complete performance tasks: the responses given by students are fully in accordance with what it is asked in performance tasks. (4) the students and the teachers have both agreed that the rubric could be well utilized for assessment purposes  (5) objective, the students relatively score similar result out of two assessment undertaken and therefore it is safe to argue that  rubric was an objective assessment. (6). Performance Assessment is seen as effective in that (a) rubric has indeed improved students performance (b) rubric paves the ways and render positive feed-backs  to effective learning due to : the students ability level  resulting from performance assessment are at Tuntas Category, and students responses to performance assessment were at positive category. (7) Reliable, the students score similar performance assessment results during the second test and as such it is concluded that rubric is has successfully produced a reliable assessment instrument. Key Words:  assesment, performance assessment, performance task, rubric